Diagnosis of Acute Pulmonary Embolism - TETİKKURT, Cüneyt (Cerrahpaşa Medical Journal, 2014)
Acute pulmonary embolism represents a potentially fatal disease. The disease presents mostly with silent or nonspecific symptoms. A number of fundamental questions continue to exist regarding the pathogenesis, clinical presentation and diagnosis. Although there is a wide range of diagnostic techniques, pulmonary embolism still remains as a diagnostic challenge for the pulmonary physicia. Therefore, in a patient with suspected pulmonary embolism, understanding the pathogenesis and clinical presentation can result in a more precise diagnosis without delay. Despite vigorous debate for optimal therapeutic approach, the majority of deaths from PE are a result of prophylactic oversight or diagnostic error.